2018
DOI: 10.1007/s10142-018-0597-9
|View full text |Cite
|
Sign up to set email alerts
|

Selection of growth-related genes and dominant genotypes in transgenic Yellow River carp Cyprinus carpio L.

Abstract: Transgenic Yellow River carp is characterized by rapid growth rate and high feed-conversion efficiency and exhibits a great application prospect. However, there is still a significant separation of growth traits in the transgenic Yellow River carp family; as such, growth-related genotypes must be screened for molecular marker-assisted selection. In this study, 23 growth-related candidate genes containing 48 SNP markers were screened through bulked segregant analysis (BSA) among transgenic Yellow River carp fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The presence of homologous genes or sequences initially complicates allele identification, however the simplicity with which SNPs can be scored promotes allele discrimination 6 . SNP markers have been widely employed in fish disease resistance 7 , 8 , feed conversion efficiency 9 , 10 , growth rate 11 , 12 , muscle yield 13 , reproductive characteristics 14 , 15 and tolerance to environmental stressors 16 , 17 since the emergence of high-throughput sequencing technology. Similarly, SNP marker-related sequencing data increased rapidly.…”
Section: Background and Summarymentioning
confidence: 99%
“…The presence of homologous genes or sequences initially complicates allele identification, however the simplicity with which SNPs can be scored promotes allele discrimination 6 . SNP markers have been widely employed in fish disease resistance 7 , 8 , feed conversion efficiency 9 , 10 , growth rate 11 , 12 , muscle yield 13 , reproductive characteristics 14 , 15 and tolerance to environmental stressors 16 , 17 since the emergence of high-throughput sequencing technology. Similarly, SNP marker-related sequencing data increased rapidly.…”
Section: Background and Summarymentioning
confidence: 99%
“…Examples are transgenic Yellow River carps (Luo et al 2018 ), engineered at the CAS Institute of Hydrobiology for a triploid expression of the fish’s growth hormone leading to a nearly twofold faster growth, and the goat Yangang, created by somatic cloning at Northwest A&F University (Zhi 2016 ).…”
Section: Biotechnology In Agriculturementioning
confidence: 99%
“…Currently, association mapping has been used extensively in the mining of excellent alleles of economic traits in livestocks (Brym et al., 2011; Justyna et al., 2017; Nalaila et al., 2012; Podisi et al., 2011) and crops (Dang et al., 2015; Wen et al., 2008; Yang et al., 2011). However, only a few studies were reported in aquaculture animals (Jiang et al., 2019; Li et al., 2020; Luo et al., 2018; Zheng et al., 2016).…”
Section: Introductionmentioning
confidence: 99%